Analisa dan Perancangan UI/UX Aplikasi Alfagift Menggunakan Metode Design Thinking: Analysis and Design of UI/UX of Alfagift Application Using Design Thinking Method - Kaunang, Stephani Gabriela; Tulenan, Virginia; Sengkey , Daniel F. (Jurnal Teknik Informatika, 2024)
Alfagift application is an e-commerce application that provides a variety of daily needs of the community that can make it easier for users to carry out the shopping process from home without having to go to the store. The problems experienced by users are the absence of features to track delivery status, limited access to contact the store so that the ordered product passes the supposed delivery hours. Based on these problems, the UI/UX of the Alfagift Application was designed using the Figma application by adding features that meet user needs and using the Design Thinking method which has 5 stages Empathize, Define, Ideate, Prototype, and Test. This research resulted in additional features the order tracking feature, contact the store through the Alfagift application, change phone numbers, delete shopping items, and change the layout on the application homepage. Based on the results that have been made, testing is carried out on 100 users with questionnaires and interviews. Through calculations using the System Usability Scale method, the results obtained with an average value of 80.75 with the Acceptable category and Excellent rating, which means that the designed interface design can be accepted by users.